2011
DOI: 10.1002/uog.10109
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of current definitions of miscarriage using mean gestational sac diameter and crown–rump length measurements: a multicenter observational study

Abstract: Objectives There is significant variation in cut-off values for mean gestational sac diameter (MSD) and embryo crown-rump length (CRL) used to define miscarriage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
100
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 16 publications
0
100
1
2
Order By: Relevance
“…Because of new recommendations for ultrasound criteria of early pregnancy failure [5][6][7] , we changed our ultrasound criteria of non-viability in 2014. Before 2014 the criteria of non-viability in our study were one of the following: (1) intrauterine gestational sac with a mean diameter > 16 mm with no embryonic pole 20 or (2) a gestational sac with an embryo with CRL ≥ 5 mm without cardiac pulsations 20 , or (3) if the above criteria were not fulfilled, a gestational sac with or without an embryo that showed no significant development at a repeat scan after 7 days 20 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of new recommendations for ultrasound criteria of early pregnancy failure [5][6][7] , we changed our ultrasound criteria of non-viability in 2014. Before 2014 the criteria of non-viability in our study were one of the following: (1) intrauterine gestational sac with a mean diameter > 16 mm with no embryonic pole 20 or (2) a gestational sac with an embryo with CRL ≥ 5 mm without cardiac pulsations 20 , or (3) if the above criteria were not fulfilled, a gestational sac with or without an embryo that showed no significant development at a repeat scan after 7 days 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Before 2014 the criteria of non-viability in our study were one of the following: (1) intrauterine gestational sac with a mean diameter > 16 mm with no embryonic pole 20 or (2) a gestational sac with an embryo with CRL ≥ 5 mm without cardiac pulsations 20 , or (3) if the above criteria were not fulfilled, a gestational sac with or without an embryo that showed no significant development at a repeat scan after 7 days 20 . After April 2014 the non-viability criteria in our study were one of the following: (1) intrauterine gestational sac with a mean diameter ≥ 25 mm with no embryonic pole or (2) a gestational sac with an embryo with CRL ≥ 7 mm without cardiac pulsations, or (3) if the above criteria were not fulfilled, a gestational sac with or without an embryo that showed no significant development at a repeat scan after 7 days 5,6,8,9 . Since all patients were managed as outpatients we did not include patients with a fetus with CRL > 33 mm because of the risk of heavy bleeding at expulsion of the pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…More recent data, particularly when considering measurement variability, have suggested that a failed intrauterine pregnancy should be diagnosed only when cardiac activity is absent in an embryo ≥7 mm, using trans-vaginal US. 2 Bilateral adnexa were scanned to rule out ectopic gestation and other pathology.…”
Section: Methodsmentioning
confidence: 99%
“…studied over one thousand pregnancies diagnosed as IPUV across four different hospitals in a multicentred prospective trial 10 . The end point was ongoing pregnancies at the 11–14 week scan.…”
Section: Methodsmentioning
confidence: 99%
“…It had been previously thought that in a normal pregnancy, the CRL should increase by approximately 1 mm per day between 7 and 12 weeks 11 23 In the fourth paper discussed here, Abdallah at el looked at a subset of the 1060 pregnancies from their main study 10 11 A total of 359 pregnancies were analysed.…”
Section: Methodsmentioning
confidence: 99%